Air Quality of Konya Province and Sustainable Ecological Urban Design Principles - Çiftçi, Çigdem; Erdem, Rahmi; Levend, Sinan (Asian Journal of Chemistry, 2011)
Turkey tends to improve social life comfort by using various imported technology. The rising of urban citizens has been negative pressure on the environmental sources such as air, water and land. Environmental pollution indicators have been affected by local governments' land use decision. A new eco-city planning model has been developed and covers three dimensions plan with the respect of social, economic and politic components. The model is originally based on the application of sustainable ecological urban design principles. The objective of this study is to examine the principles of the eco-city planning for Konya province in order to determine life quality and city health. The data were collected from 4 different areas of Konya in 97.9 hectares and carried GIS platform. The tropospheric SO2 and PM10 levels for 2006 were associated in the pollution maps. Air pollution levels in the area were compared with according to the air quality conservation legislation (HKKY) in Turkey and Directive 1999/30/EC in EU, as well as WHO's air quality guidelines (AQGs). As the study results, some proposes have been recommended for local government where life quality and city health increase.